1987
DOI: 10.2172/6124450
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid biosynthesis in Euphorbia lathyris and Copaifera spp

Abstract: Biosynthesis of triterpenoids (triterpene esters and triterpenols) by isolated latex ofEuphorbia lathyris was investigated. The rate of in vitro incorporation of mevalonic acid (0.55 nmol 100 p.1 latex 1 h-1 ) into triterpenoids was thirty times greater than acetate incorporation (0.02 nmol 100 41 latex 1 tn), indicating that the rate-limiting step in the pathway occurs prior to mevalonate. A particulate fraction, capable of converting mevalonate but not acetate into triterpenoids (15,000g pellet), showed a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…From our early observation of E. kansui Liou laticifers at early developmental stages, some endoplasmic reticulum dilated and coalesced to form small vacuoles, which began to accumulate latex particles, and then transport and release these latex particles into the central vacuole with their coalesce [37]. Skrukrud reported that mevalonic acid synthesize triterpenoid in the small vacuole of laticifers in Euphorbia Lathyri [38]. Fineran's ullrastructural observations indicated that latex particles were synthesized in tubular vacuoles in the peripheral cytoplasm of developing E. pulcherrima laticifers [39].…”
Section: Immunoblotting and Subcellular Localization Of Ehmdcmentioning
confidence: 99%
“…From our early observation of E. kansui Liou laticifers at early developmental stages, some endoplasmic reticulum dilated and coalesced to form small vacuoles, which began to accumulate latex particles, and then transport and release these latex particles into the central vacuole with their coalesce [37]. Skrukrud reported that mevalonic acid synthesize triterpenoid in the small vacuole of laticifers in Euphorbia Lathyri [38]. Fineran's ullrastructural observations indicated that latex particles were synthesized in tubular vacuoles in the peripheral cytoplasm of developing E. pulcherrima laticifers [39].…”
Section: Immunoblotting and Subcellular Localization Of Ehmdcmentioning
confidence: 99%